Teaching Service Commission annual report 2020 - Trinidad and Tobago. Teaching Service Commission (Service Commissions Department, 2020)
This is the report of the Teaching Service Commission (TSC) for the period 1st January 2020 to 31st December 2020.
The Teaching Service Commission (TSC) was established under the Constitution of the Republic of Trinidad and Tobago (Section 124) and its mandate is stated in Section 125 thereof: Subject to the provisions of this Constitution, power to appoint persons to hold or act in public offices in the Teaching Service established under the Education Act, including power to make appointments on promotions and transfer and to confirm appointments, and to remove and exercise disciplinary control over persons holding or acting in such offices and to enforce standards of conduct on such officers shall vest in the Teaching Service Commission.